Método de Prick-test en la etiología de la rinitis alérgica infantil. Centro Asma-Alergias Muñoz, 2018 - Gagñay Angamarca, Josselyn Elizabeth (2019)
allergic rhinitis is inflammation of the nasal mucosa caused by allergens present in the environment, causing symptoms such as rhinorrhea, nasal congestion, sneezing and itching. This disease is a serious health problem worldwide, affecting approximately more than 500 million people; the most affected population are children affect their quality of life and well-being. Objective: Identify the main etiological agents that cause allergic rhinitis using the Prick-test method in children from 6 months to 12 years who come to the outpatient clinic of the Muñoz Asthma and Allergies Center, year 2018. Material and methods: The study was conducted based on the research methodology with a descriptive, retrospective and field study in a universe of 102 patients, obtaining information from various sources. To obtain the data, clinical records, patient records and laboratory record of prick-test of the Asthma and Allergies Center, they were reviewed. Results: Of the 102 patients in the study with a diagnosis of allergic rhinitis, the main etiological agents that were detected through the prick-test method are pollen with 34.3%, followed by 33.3% by dust mites, 24.5% by fungi and 7.8% by domestic animals. Conclusion: The principal etiological agent detected by the method of Prick-test that causes allergic rhinitis in children from 6 months to 12 years of the Muñoz Asthma and allergies Center, they were pollens.